Unemployment and Right-Wing Extremist Crime - Armin Falk; Josef Zweimüller (Institute for the Study of Labor (IZA), 2005)
Right-wing extremism is a serious problem in many societies. A prominent hypothesis states that unemployment plays a crucial role for the occurrence of right-wing extremist crime. In this paper we empirically test this hypothesis. We use a previously not used data set which includes all officially recorded right-wing criminal acts in Germany. These data are recorded by the German Federal Criminal Police Office on a monthly and state level basis. Our main finding is that there is in fact a significant positive relation between unemployment and rightwing criminal activities. We show further that the big difference in right-wing crime between East and West German states can mostly be attributed to differences in unemployment. This finding reinforces the importance of unemployment as an explanatory factor for right-wing crime and questions explanations based solely on the different socialization in former communist East Germany and the liberal West German states. Our data further allow us to separate violent from non-violent right-wing crimes. We show that unemployment is closely related to both types of crimes, but that the association with non-violent crimes is much stronger. Since right-wing crime is committed particularly by relatively young males, we also explore whether the youth unemployment rate is a better predictor for right-wing crime than total unemployment. This hypothesis can be rejected: given total unemployment, a higher share of youth unemployment does not affect right-wing extremist crime rates.
Keywords: J60; J15; K14; 330; hate crime; right-wing extremism; unemployment; cost of unemployment